Quelle définition pour le flou interpellatif ? - Liana Pop (Corela)
What definition for the loose category of “interpellation” (‘summoning’) in French? Even if in this research we try to give a linguistic definition of the “interpellation”, the category remains questionable and imposes a very broad perspective because in French, “interpellation” someone means calling out to,shouting at, commanding, addressing somebody in a reproachful manner, whether you name the person or not. There are a great number of synonyms to “interpellation”, anf for a more or less direct manifestation of it, we can enumerate: linguistic and non-linguistic (non-verbal) summoning; propositional or non-propositional, nominal, verbal, and interjectional summoning; summoning as an act or non-act, dialogic or polyphonic; in trilogue or polylogue situations, cancelled summoning, etc. – the last ones defined as “tropes communicationnels”. We will conclude in favour of a natural loose and multi-criteria category (not an expert one), having more or less prototypical forms. The examples are taken from a French and Romanian oral corpus.